2023
DOI: 10.1038/s41467-023-36133-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel oxygen reservoirs increase functional integration of neural stem cell grafts by meeting metabolic demands

Abstract: Injectable biomimetic hydrogels have great potential for use in regenerative medicine as cellular delivery vectors. However, they can suffer from issues relating to hypoxia, including poor cell survival, differentiation, and functional integration owing to the lack of an established vascular network. Here we engineer a hybrid myoglobin:peptide hydrogel that can concomitantly deliver stem cells and oxygen to the brain to support engraftment until vascularisation can occur naturally. We show that this hybrid hyd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…It is also important to achieve the desired effect by complementing different functions. Myoglobin (Mb) has great potential to improve cell transplantation outcomes, but they cannot reach specific sites on their own (Y. Wang et al., 2023). Binding of Mb to peptide hydrogels positively affects cell survival, integration, and differentiation.…”
Section: Synthesis Methods and Functionalization Of Peptide Hydrogelsmentioning
confidence: 99%
“…It is also important to achieve the desired effect by complementing different functions. Myoglobin (Mb) has great potential to improve cell transplantation outcomes, but they cannot reach specific sites on their own (Y. Wang et al., 2023). Binding of Mb to peptide hydrogels positively affects cell survival, integration, and differentiation.…”
Section: Synthesis Methods and Functionalization Of Peptide Hydrogelsmentioning
confidence: 99%
“…Reperfusion (after 1 ​h of occlusion) BMSCs (5 ​× ​10 5 ​cells/10 ​μL) Into the perilesional site 10 ​ml 26 s-gauge, Hamilton, for 10 ​min 1 24 h after MCAO 1% DF-PEG4000 with 3% GC (1:3), and 5 ​mg/ml nanofibers loaded in the hydrogel None After 2 weeks: Significant neurogenesis and angiogenesis The reduction of ischemic brain damage, infarct volume, microglial and astrocyte overactivation, and neurological deficits Pei-2023 [ 193 ] Ncad-mRADA, Self-assembled NSE-DTA mice, Wild-type Institute of Cancer Research mice, C57BL/6J mice, and Dcx-EGFP mice 8–16-weeks None 1%–3% isoflurane in oxygen Ischemic stroke, MCAO was induced by the intraluminal filament technique 10 ​mm silicone-coated 8 filament, 40 ​min later filament was withdrawn None Into the site 2.5 ​μL–3 ​μL 3. Glass capillary needle, slowly stereotaxically injected 1 13 ​± ​1 day-post MCAO micce and 2 days-post-cryoinjured mice 0.5% v/v 7.4 Neuroblast migration to the injured site in the striatum Neuronal regeneration Functional recovery improvement in neonates with cortical brain damage Ohno-2023 [ 194 ] Fmoc-DDIKVAV, Self-assembled Mouse/C57BL/6 Adult None 2% isoflurane TBI Via stereotaxic frame, craniotomy Myoglobin (1 ​mg/mL) and/or cortical neural stem cells, (5 ​× ​10 4 /μl cells) Into the striatum 2 ​μl microinjection 1 None 15 ​mg/mL None After 4 weeks: Assist engraftment by supply oxygen and stem cells to the brain simultaneously Established vascular network Significant improvement in neuronal differentiation Greater functional integration of stem cell-derived grafts Wang-2023 [ 195 ] RADA16; <...…”
Section: Injectable Hydrogelsmentioning
confidence: 99%
“…Moreover, including myoglobin in the hydrogel resulted in greater innervation of the host tissue by the grafted cells, which is required for neuronal replacement procedures to ensure adequate synaptic formation. It was mentioned that this strategy could improve the functional integration of stem cell-derived grafts for treating central and peripheral nervous system injuries and disorders [ 195 ].…”
Section: Injectable Hydrogelsmentioning
confidence: 99%
“…Oxygen- and nutrient-carrying hydrogels have been designed to maintain a favourable environment for transplanted MSCs. Different approaches of short- and long-term oxygenation exist to increase stem cell survival and therapeutic efficacy, such as the use of hyperbaric oxygenation to systemically deliver oxygen; 201 in situ oxygen generation with MgO 2 , 202 CaO 2 , 203 and H 2 O 2 ; 204,205 and material functionalisation with oxygen carriers, such as hemoglobin, 206 myoglobin, 207 and fluorinated compounds such as perfluorocarbons (PFC). 208 Niu et al have reported that under 1% O 2 condition, MSCs encapsulated in a PFC-carrying hydrogel show significantly improved cell survival and proliferation over unprotected MSCs for 14 days, further highlighting the importance of oxygenation during biomaterial-based stem cell transplantation.…”
Section: Biomaterials For Msc Transplantationmentioning
confidence: 99%